Total organic carbon disappearance kinetics for supercritical water oxidation of dimethyl methylphospate used as a chemical agent simulant - Lee, BM; Veriansyah, B; Kim, SH; Kim, JD; Lee, YW (KOREAN INSTITUTE CHEMICAL ENGINEERS, 2005)
Supercritical Water Oxidation (SCWO) has been proven to be a powerful technology to treat a wide range of wastes, but there are few references in the literature about the application of SCWO to chemical weapon agents. In this work, SCWO has been tested to treat a chemical agent stimulant, dimethyl methylphosphonate (DMMP), which is similar to the nerve agent VX and GB (Sarin) in its structure. The experiments were performed in an isothermal tubular reactor with H2O2 as an oxidant. The reaction temperatures ranged from 398 to 633 degrees C at a fixed pressure of 24 MPa. The conversion of DMMP was monitored by analyzing total organic carbon (TOC) on the liquid effluent samples. It was found that the oxidative decomposition of DMMP proceeded rapidly and a high TOC decomposition up to 99.99% was obtained within I I seconds at 555 degrees C. An assumed first-order global power-law rate expression was determined with activation energy of 32.35 +/- 2.21 kJ/mol and a pre-exponential factor of 54.63 +/- 1.45 s(-1) to a 95% confidence level. By taking into account the dependence of the reaction rate on oxidant concentration, a global power-law rate expression was regressed from the complete set of data. The resulting activation energy was 42.00 +/- 0.41 kJ/mol; the pre-exponential factor was 66.56 +/- 0.48 l(1.31) mmol(-0.31) s(-1); and the reaction orders for DMMP (based on TOC) and oxidant were 0.96 +/- 0.02 and 0.35 +/- 0.04, respectively.
Keywords: PHENOL OXIDATION; DECOMPOSITION